Projeto de um transceptor FSK - Gomes, José Victor Magalhães (Universidade Federal Rural do Semi-Árido, 2019)
In this work, it proposes the development of the design of the FSK transceiver with low error rate, low transmission rate, good robustness to the noise and greater simplicity of the circuit. In this work na FSK transceiver with componentes easily found in the market is proposed. The modulator circuit and the demodulator circuit were simulated in the LTspice XVII software and results were obtained from the design calculations for the 1 kHz and 10 kHz central frequencies of the modulator and demodulator circuit. The modulator and the demodulator were tested experimentally and compared with the results obtained in theory and simulation. Simulated and practical results have proven the efficiency of the designed transceiver.
Monografia
Keywords: Modulador; Demodulador; Amplificadores operacionais; Modulações digitais; Modulator; Demodulator; Operational amplifiers; Digital modulations; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA